Topographical and geological factors on gully-type debris flow in Malai River catchment, Siwaliks, Nepal (Journal of Nepal Geological Society, 2019)
The Siwalik hill of Nepal lies in between the two major thrusts; Main boundary Thrust and Main Frontal Thrust. Thrusting and continuous erosion of material from surface causes several landslides and debris flow problem in the Siwalik region. Debris flow commonly occurs after landslide during heavy rainfall in the steep slope. This paper described about the topographical and geological controls on debris flow occurring in gullies in the Siwaliks of the Malai River catchment of mid-Western Nepal. The length of gully, length of debris channel, area of debris channel, area of catchment of debris flow, area of gully without debris flow were found using Google earth pro, a free version online database. Similarly, a form factor (F), average gradient of stream, slope area ratio and a topographical factor (T) were calculated. Lithology and geological structure were studied in the field. The relation between each factor was identified.Gully having larger debris flow event had T value greater than 0.01 and that having small debris flow event had T value less than 0.01. Gully without debris flow had T value less than 0.001. Gully having debris flow had F more than 0.1 and that free from debris flow had F less than 0.1. Both topographic and form factors were found greater than 0.1 at the hanging wall of the Malai Thrust, where large size debris flows were encountered. The T and F values obtained from the Middle and Upper Siwaliks were greater than 0.1.The number of debris flow events and large debris flows were found high the in the Middle and the Upper Siwaliks, and hanging wall of the Malai Thrust.